Preparation process and application of modified biodegradable polylactic acid
By adding nano CeO2 and SiO2 particles to polylactic acid resin and polyhydroxy fatty acid ester, a composite film with improved ultraviolet barrier properties and good mechanical properties was prepared, which solved the shortcomings of the existing polylactic acid films in ultraviolet barrier functions, and achieved effective protection and environmentally friendly biodegradability for patients with skin diseases.
Patent Information
- Application Number
- CN202510071910.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polylactic acid films are limited in terms of ultraviolet barrier function and cannot effectively protect patients with skin diseases from ultraviolet irritation.
By adding nano CeO2 and SiO2 particles to polylactic acid resin and polyhydroxy fatty acid ester, composite films with improved ultraviolet barrier properties, good mechanical properties and biodegradability were prepared.
It significantly improves the ultraviolet resistance of the film, provides effective protection for patients with skin diseases, and has good biodegradability, which meets the requirements of sustainable development.
Smart Images

Figure CN119505321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biodegradable films, to a preparation process and application of modified biodegradable polylactic acid, and in particular to the preparation of a polylactic acid resin / polyhydroxyalkanoate film doped with SiO2 and CeO2 composite nanoparticles for UV protection of skin diseases. Background Art
[0002] Ultraviolet rays can cause great irritation to patients with skin diseases. When ultraviolet rays irradiate the patient's skin, it causes vasodilation and red and itchy skin. Excessive exposure can cause erythema and form blisters and edema. For example, actinic dermatosis and lupus erythematosus. These diseases are caused by phototoxicity or photoallergic reactions that cause sunlight to act on the organism, and sunlight exposure can aggravate the condition. Therefore, patients usually take some measures to avoid the damage caused by ultraviolet rays when exposed to direct sunlight, such as physical sunscreen and chemical methods. However, for chemical sunscreen, many patients are allergic to sunscreen or sunscreen spray, so physical sunscreen is particularly important. In addition, for patients who exercise, physical sunscreen forms such as parasols are not acceptable. Therefore, it is of great significance to develop a protective barrier UV film that can be applied to patients. With the increasing global attention to environmental protection, the research and development and application of biodegradable films have become a research hotspot. Polylactic acid (PLA), as a biodegradable thermoplastic polyester, has good biocompatibility, degradability and mechanical properties, and is widely used in packaging, medical, agriculture and other fields. However, PLA also has some disadvantages, such as slow crystallization rate, low crystallinity, poor heat resistance, etc., which limit its application in some fields. A common strategy for studying the crystallization rate and heat resistance of PLA is to modify it by filling it with inorganic materials. In recent years, rare earth oxides have played an important role in polymer modification due to their high thermal stability, good hydrophobicity and low thermal expansion coefficient. For example, it has been shown that La2O3 and Y2O3 can significantly increase the crystallization rate of polypropylene. Therefore, the functionalized application of rare earth oxide-like polylactic acid has development value.
[0003] At present, researchers' functional modification of polylactic acid mainly focuses on mechanical properties, thermal properties and crystallization rate, while there is little research on its UV blocking function. Although polylactic acid has good applications in contact with human skin due to its good biocompatibility, its UV blocking function is limited and cannot be used for UV protection of patients. Therefore, the development of polylactic acid films with UV blocking function has potential application value. Polyhydroxyalkanoates (PHA), as a class of biodegradable polyesters synthesized by microorganisms, have good biocompatibility, thermal processability and biodegradability, and their degradation products are environmentally friendly, which has significant advantages in environmental sustainability. It can be produced by a variety of microbial fermentation processes, and the raw materials are widely sourced, including sugars, fatty acids, etc., which makes it possible for large-scale industrial production. It has been used in the research and application of tissue engineering scaffolds, drug sustained-release carriers, etc. in the biomedical field. In addition, for rare earth oxides, cerium oxide and silicon oxide have attracted much attention in recent years due to their abundant reserves and excellent physical and chemical properties. On the one hand, cerium oxide and silicon oxide can affect the optical properties of the film by changing the refractive index of the film. On the other hand, cerium oxide has good ultraviolet absorption and protection functions. Based on the biodegradable characteristics of PHA and PLA and the excellent ultraviolet protection performance of SiO2 and CeO2, mixing SiO2 and CeO2 particles with PHA and PLA resins to prepare ultraviolet protection films has important research significance and broad application prospects. This composite film can not only meet the requirements for ultraviolet protection, but also degrade naturally after use, reduce pollution to the environment, and conform to the current development trend of green environmental protection materials. The present invention prepares cerium oxide / polylactic acid / composite materials, and studies the ultraviolet transmittance, mechanical properties and biodegradability of the film. Summary of the invention
[0004] The present invention provides a preparation process and application of modified biodegradable polylactic acid, and a preparation method of a biodegradable polylactic acid / polyhydroxyalkanoate film modified by composite nanoparticles, wherein the film has the performance of blocking ultraviolet transmission, good mechanical properties and excellent biodegradability. The method comprises the following steps:
[0005] S1. First, polylactic acid resin (PLA), polyhydroxyalkanoate (PHA), nano-CeO2 particles, and nano-SiO2 particles are uniformly blended in a certain proportion, wherein the mass ratio of PHA to PLA is 1:1, the mass ratio of the added nano-CeO2 particles and nano-SiO2 particles is 1:1, and the total particle ratio is 0.8-1.6%. Add them into a torque rheometer, melt-blend them at a suitable temperature and rotation speed for a certain time, and prepare a blend.
[0006] S2. Then, the blend obtained in step S1 is placed on a flat vulcanizer, and a mold of a certain thickness is used to control the film thickness. After preheating at 160-180°C for 6-30 min, the blend sample is hot-pressed at a pressure of 10MPa-20MPa and the film is collected.
[0007] S3. Finally, the hot-pressed film is placed together with the mold on the cold pressing plate of the flat vulcanizer, and the film is cold pressed with a relatively high pressure to finally obtain a composite film material.
[0008] Preferably, the temperature of the torque rheometer in step S1 is 180°C-200°C.
[0009] Preferably, the rotation speed of the torque rheometer in step S1 is 50 rpm-100 rpm.
[0010] Preferably, the added nano CeO2 particles and nano SiO2 particles have a mass ratio of 1:1, and the total particle ratio is 1.2%-1.6%, which significantly improves the mechanical properties of the resin and the UV penetration resistance;
[0011] Preferably, in step S2, the blend obtained in step S1 is placed on a flat vulcanizer at a temperature of 180°C-200°C.
[0012] Preferably: in step S2, the thickness of the prepared mold is 0.08 mm-0.2 mm.
[0013] Preferably, in step S2, the flat plate vulcanizing press is preheated at 160° C. for 30 minutes.
[0014] Preferably, in step S2, the flat plate vulcanizer is preheated at 180°C for 6 minutes.
[0015] Preferably, in step S2, the blend sample is hot pressed for 1 min to 10 min.
[0016] Preferably, in step S3, the hot-pressed film is naturally cooled at room temperature to be fully solidified and then placed on the cold pressing plate of the flat vulcanizer. During the cooling process, the film should be prevented from being squeezed or collided by external forces to ensure the flatness and dimensional stability of the film.
[0017] Preferably, in step S3, the pressure of the plate vulcanizing press is controlled to be 10 MPa-20 MPa.
[0018] Preferably: in S3, the temperature of the cold pressing plate is maintained at room temperature 20°C-25°C.
[0019] Preferably: the modified biodegradable polylactic acid film obtained by the above-mentioned preparation process of modified biodegradable polylactic acid is used in the preparation of sunscreen products.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention significantly improves the anti-ultraviolet performance of the resin by adding nano CeO2 and SiO2 particles to polylactic acid resin / polyhydroxyalkanoate, providing effective protection for patients with skin diseases; at the same time, it has good mechanical properties.
[0022] 2. The polylactic acid resin / polyhydroxyalkanoate film modified with CeO2 and SiO2 has good biodegradability, will not pollute the environment, and meets the requirements of sustainable development.
[0023] 3. The preparation method is simple and easy, with low cost, and is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scan of the nano CeO2 used in the present invention. From the scan, it can be seen that the diameter of the CeO2 used is about 200nm, and the shape presents a regular sphere.
[0025] Figure 2 This is a transmission image of the nano-SiO2 used in the present invention. From the scanning image, it can be seen that the diameter of the SiO2 used is about 100nm, and the shape also presents a regular spherical shape.
[0026] Figure 3 It is a bar chart of the tensile strength of the films obtained in Example 4 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0027] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0028] Some of the raw materials used in the present invention are: polylactic acid resin (Nature Works, USA, specification 3001D), polyhydroxyalkanoate (Wuhan Jiyesheng Chemical Co., Ltd., product number EM10080), nano CeO2 particles (Hunan Rare Earth Metal Materials Research Institute, specification 99.99%) and nano SiO2 particles (Wuhan Jiyesheng Chemical Co., Ltd., specification 99.99%).
[0029] Example 1
[0030] S1. Prepare PC-0.2 film according to mass percentage, and prepare PC-0.2 according to the method in the above specific embodiment, wherein the mass percentage of polylactic acid resin / polyhydroxyalkanoate is 99.8%, the mass percentage of CeO2 is 0.1%, and the mass percentage of SiO2 is 0.1%.
[0031] Firstly, a substrate was prepared with a mass ratio of PHA to PLA of 1:1, and then the mixture was uniformly blended in a ratio of (PHA+PLA):(CeO2+SiO2)=99.8:0.2. The mixture was added into a torque rheometer and melt-blended at 180 °C and 100 rpm for 20 min to prepare a PC-0.2 blend.
[0032] S2. Then, the obtained blend was placed on a flat vulcanizer at a temperature of 180°C, and a mold with a thickness of 0.12 mm was used to control the film thickness. After preheating at 180°C for 6 min, the blend sample was hot-pressed at a pressure of 20 MPa for 5 min and the film was collected.
[0033] S3. Finally, the hot-pressed film and the mold are naturally cooled at room temperature. After the film is fully solidified and shaped, it is placed on the cold pressing plate of a flat vulcanizer. The temperature of the cold pressing plate is maintained at room temperature 25°C. The film is cold pressed at a pressure of 20 MPa to finally obtain a composite film material.
[0034] Example 2
[0035] S1. Prepare PC-0.4 film according to mass percentage, and prepare PC-0.4 according to the method in the above specific embodiment, wherein the mass percentage of polylactic acid resin / polyhydroxyalkanoate is 99.6%, the mass percentage of CeO2 particles is 0.2%, and the mass percentage of SiO2 particles is 0.2%.
[0036] Firstly, a substrate was prepared with a mass ratio of PHA to PLA of 1:1, and then the mixture was uniformly blended in a ratio of (PHA+PLA):(CeO2+SiO2)=99.6:0.4. The mixture was added into a torque rheometer and melt-blended at 180 °C and 100 rpm for 20 min to prepare a PC-0.4 blend.
[0037] S2. Then, the obtained blend was placed on a flat vulcanizer at a temperature of 180°C, and a mold with a thickness of 0.12 mm was used to control the film thickness. After preheating at 180°C for 6 min, the blend sample was hot-pressed at a pressure of 20 MPa for 5 min and the film was collected.
[0038] S3. Finally, the hot-pressed film and the mold are naturally cooled at room temperature. After the film is fully solidified and shaped, it is placed on the cold pressing plate of a flat vulcanizer. The temperature of the cold pressing plate is maintained at room temperature 25°C. The film is cold pressed at a pressure of 20 MPa to finally obtain a composite film material.
[0039] Example 3
[0040] S1. Prepare PC-0.8 film according to mass percentage, and prepare PC-0.8 according to the method in the above specific embodiment, wherein the mass percentage of polylactic acid resin / polyhydroxyalkanoate is 99.2%, the mass percentage of CeO2 is 0.4%, and the mass percentage of SiO2 is 0.4%.
[0041] Firstly, a substrate was prepared with a mass ratio of PHA to PLA of 1:1, and then the mixture was uniformly blended in a ratio of (PHA+PLA):(CeO2+SiO2)=99.2:0.8. The mixture was added into a torque rheometer and melt-blended at 180 °C and 100 rpm for 20 min to prepare a PC-0.8 blend.
[0042] S2. Then, the obtained blend was placed on a flat vulcanizer at a temperature of 180°C, and a mold with a thickness of 0.12 mm was used to control the film thickness. After preheating at 180°C for 6 min, the blend sample was hot-pressed at a pressure of 20 MPa for 5 min and the film was collected.
[0043] S3. Finally, the hot-pressed film and the mold are naturally cooled at room temperature. After the film is fully solidified and shaped, it is placed on the cold pressing plate of a flat vulcanizer. The temperature of the cold pressing plate is maintained at room temperature 25°C. The film is cold pressed at a pressure of 20 MPa to finally obtain a composite film material.
[0044] Example 4
[0045] S1. Prepare PC-1.2 film according to mass percentage, and prepare PC-1.2 according to the method in the above specific embodiment, wherein the mass percentage of polylactic acid resin / polyhydroxyalkanoate is 98.8%, the mass percentage of CeO2 is 0.6%, and the mass percentage of SiO2 is 0.6%.
[0046] Firstly, a substrate was prepared with a mass ratio of PHA to PLA of 1:1, and then the mixture was uniformly blended in a ratio of (PHA+PLA):(CeO2+SiO2)=98.8:1.2. The mixture was added into a torque rheometer and melt-blended at 180 °C and 100 rpm for 20 min to prepare a PC-1.2 blend.
[0047] S2. Then, the obtained blend was placed on a flat vulcanizer at a temperature of 180°C, and a mold with a thickness of 0.12 mm was used to control the film thickness. After preheating at 180°C for 6 min, the blend sample was hot-pressed at a pressure of 20 MPa for 5 min and the film was collected.
[0048] S3. Finally, the hot-pressed film and the mold are naturally cooled at room temperature. After the film is fully solidified and shaped, it is placed on the cold pressing plate of a flat vulcanizer. The temperature of the cold pressing plate is maintained at room temperature 25°C. The film is cold pressed at a pressure of 20MPa to finally obtain a composite film material.
[0049] Comparative Example 1: The CeO2 particles in the above step S1 are replaced with SiO2 particles, that is, the CeO2 particles are removed and only 1.2% SiO2 particles are added, and the remaining steps are the same as those in Example 4.
[0050] Comparative Example 2: The polylactic acid resin / polyhydroxyalkanoate in the above step S1 is replaced with polylactic acid resin, that is, the polyhydroxyalkanoate is removed and only 98.8% of polylactic acid resin is added, and the remaining steps are the same as those in Example 4.
[0051] Comparative Example 3: The polylactic acid resin / polyhydroxyalkanoate in the above step S1 is replaced by polyhydroxyalkanoate, that is, the polylactic acid resin is removed and only 98.8% polyhydroxyalkanoate is added, and the remaining steps are the same as those in Example 4.
[0052] Comparative Example 4: The SiO2 particles in the above step S1 are replaced with CeO2 particles, that is, the SiO2 particles are removed and only 1.2% CeO2 particles are added, and the remaining steps are the same as those in Example 4.
[0053] Example 5
[0054] S1. Prepare PC-1.6 film according to mass percentage, and prepare PC-1.6 according to the method in the above specific embodiment, wherein the mass percentage of polylactic acid resin / polyhydroxyalkanoate is 98.4%, the mass percentage of CeO2 is 0.8%, and the mass percentage of SiO2 is 0.8%.
[0055] Firstly, a substrate was prepared with a mass ratio of PHA to PLA of 1:1, and then the mixture was uniformly blended in a ratio of (PHA+PLA):(CeO2+SiO2)=98.4:1.6. The mixture was added into a torque rheometer and melt-blended at 180 °C and 100 rpm for 20 min to prepare a PC-1.6 blend.
[0056] S2. Then, the obtained blend was placed on a flat vulcanizer at a temperature of 180°C, and a mold with a thickness of 0.12 mm was used to control the film thickness. After preheating at 180°C for 6 min, the blend sample was hot-pressed at a pressure of 20 MPa for 5 min and the film was collected.
[0057] S3. Finally, the hot-pressed film and the mold are naturally cooled at room temperature. After the film is fully solidified and shaped, it is placed on the cold pressing plate of a flat vulcanizer. The temperature of the cold pressing plate is maintained at room temperature 25°C. The film is cold pressed at a pressure of 20 MPa to finally obtain a composite film material.
[0058] 1. Transmittance of the sample
[0059] Test method:
[0060] The transmittance of the films obtained in Examples 1-5 and Comparative Examples 1-4 in the range of 200-800 nm was characterized using a UV-visible-near infrared spectrophotometer (Cary 5000, Santa Clara, CA, USA). The calculation formula for UVA transmittance is:
[0061]
[0062] Where T u is the average UVA transmittance, T w is the UVA transmittance at a certain point between 320 nm and 400 nm, and m is the number of points at which the UVA transmittance is tested in the wavelength range of 320 to 400 nm. The results are shown in Table 1.
[0063] Table 1 Transmittance of films with different cerium oxide and silicon dioxide contents under long-wave ultraviolet light in Examples 1 to 5 of the present invention.
[0064] Group Sample UVA transmittance / % Example 1 PC-0.2 63.46 Example 2 PC-0.4 25.37 Example 3 PC-0.8 3.84 Example 4 PC-1.2 0.32 Example 5 PC-1.6 0.81 Comparative Example 1 10.54 Comparative Example 2 13.88 Comparative Example 3 15.76 Comparative Example 4 8.49
[0065] It can be seen from Table 1 that as the content of cerium oxide and silicon dioxide increases, the transmittance of the sample gradually decreases. In addition, the transmittance of PC-1.2 is the lowest. Due to the problem of particle agglomeration, the transmittance of the sample PC-1.6 obtained when the doping concentration increases to 1.6% is higher than that of PC-1.2. It can be seen that when the total addition amount of cerium oxide and silicon dioxide is 0.8-1.6%, especially 1.2%, the transmittance of the obtained film is the lowest and the UV protection performance is the best.
[0066] Compared with comparative examples 1-4, the transmittance of Example 4 is significantly lower than that of comparative examples 1-4, indicating that the synergistic effect of CeO2, SiO2, polylactic acid resin, and polyhydroxyalkanoate significantly improves the UV protection performance.
[0067] 2. Biodegradability Test
[0068] Test method:
[0069] To evaluate the degradation of the film at room temperature, the film samples obtained in Examples 3-5 and Comparative Examples 1-4 were immersed in a 0.01 mol / L NaOH solution for 28 days to determine the degradation rate of the samples. Degradation rate calculation formula:
[0070]
[0071] Where M0 represents the initial content of the film, and M1 represents the remaining mass after degradation over a period of time.
[0072] The results are shown in Table 2.
[0073] Table 2 Biodegradability test of different biodegradable modified polylactic acid films
[0074] Group Degradation rate of film after 28 days / % Example 3 42.56 Example 4 44.25 Example 5 42.95 Comparative Example 1 40.17 Comparative Example 2 39.39 Comparative Example 3 39.65 Comparative Example 4 38.74
[0075] As shown in Table 2, the degradation rate of Example 4 (sample PC-1.2) after being immersed in a 0.01 mol / L NaOH solution for 28 days is as high as 44.25%, which is the highest among all samples.
[0076] 3. Mechanical properties test
[0077] Before testing, the films obtained in Example 4 and Comparative Examples 1-4 were treated at room temperature with a relative humidity of 50% for at least 24 hours. The tensile properties of all films were tested using a universal material testing machine (Instron 2365, Darmstadt, Germany). The test was carried out in accordance with the GBT1040.3-20061B plastic tensile properties test standard, and the experimental tensile rate was set to 50 mm / min. Each sample was measured at least five times, and the results were averaged. The results are shown in Figure 2. Figure 3 shown.
[0078] Depend on Figure 3 It can be seen that the tensile strength of Example 4 (sample PC-1.2) is as high as 48.45 MPa, which is higher than the tensile strength of the samples in which SiO2 or CeO2 particles, polylactic acid resin or polyhydroxyalkanoate substrate are added separately in Comparative Examples 1-4, indicating that the synergistic effect of CeO2, SiO2, polylactic acid resin and polyhydroxyalkanoate makes the mechanical properties of the sample better.
[0079] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A process for preparing modified biodegradable polylactic acid, characterized in that: Its specific The preparation steps are as follows: S1, mixing process: adding polylactic acid resin, polyhydroxyalkanoate, nano CeO2 particles, and nano SiO2 particles into the torque rheometer in proportion, and mixing them thoroughly at a temperature of 180 ℃-200 ℃ and a rotation speed of 50 rpm-100 rpm; S2, placing the blend obtained in step S1 on a flat vulcanizer, and using a mold with a thickness of 0.08 mm-0.2 mm to control the film thickness, and after preheating, hot pressing the blend sample at a pressure of 10 MPa-20 MPa to collect the film; S3. Place the hot-pressed film together with the mold on the cold pressing plate of a flat vulcanizer, and cold press the film at a pressure of 10 MPa-20 MPa to finally obtain a composite film material.
2. A process for preparing a modified biodegradable polylactic acid according to claim 1, characterized in that: In step S1, a composite resin matrix is prepared, and the mass ratio of polylactic acid resin and polyhydroxyalkanoate added is controlled to be 1:
1.
3. A process for preparing a modified biodegradable polylactic acid according to claim 1, characterized in that: In step S1, the mass ratio of the added nano-CeO2 particles to the nano-SiO2 particles is 1:1, and the total particle proportion is 0.8%-1.6%.
4. A process for preparing a modified biodegradable polylactic acid according to claim 1, characterized in that: In step S3, the hot-pressed film is naturally cooled at room temperature to be fully solidified and then placed on a cold pressing plate of a flat vulcanizer.
5. According to the process for preparing a modified biodegradable polylactic acid as claimed in claim 1, in step S2, the blend obtained in step S1 is placed on a flat vulcanizer at a temperature of 180°C-200°C.
6. According to the process for preparing modified biodegradable polylactic acid as claimed in claim 1, in step S2, the flat plate vulcanizer is preheated at 160-180°C for 6-30 minutes.
7. According to the process for preparing a modified biodegradable polylactic acid as claimed in claim 1, in step S3, the temperature of the cold press plate is maintained at room temperature 20°C-25°C.
8. A modified biodegradable polylactic acid film obtained by the preparation process of a modified biodegradable polylactic acid as described in any one of claims 1 to 7.
9. Use of a modified biodegradable polylactic acid film obtained by the preparation process of a modified biodegradable polylactic acid as described in any one of claims 1 to 7 in the preparation of sunscreen products.
Citation Information
Patent Citations
Polyhydroxylkanoates as well as blending modification for copolymer thereof and polylactic acid
CN101205356A
Silica-cerium oxide composite particle, its production and resin composition and cosmetic containing the same
JP1997118610A
Resin composition and molded article using the same
JP2010202757A
Dental clamp for easy tooth preparation and dental clamp assembly having the dental clamp
KR102636529B1
Composition based on agro-based biodegradable polymers
WO2015092257A1